2006
DOI: 10.1007/s10826-006-9097-y
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Multiple Family Group Intervention for Juvenile First Offenders in Reducing Parent Stress

Abstract: Parenting practices are major influences on incidents of juvenile delinquency. Stress experienced by parents of children with behavioral problems is a leading contributor to parenting practices. We investigated the extent to which parental stress was reduced by participation in an established multiple group family intervention, the Family Solutions Program, developed to reduce recidivism among juvenile offenders. We also examined parent stress by gender, ethnicity, dropout rates, intervention benefits at 3-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…39 Specifically, Family APGAR score of 0-3 is considered to be high dysfunctionality, 4-6 is moderate dysfunctionality, and 7-10 is good functionality. 40 In the present study, the Cronbach's α coefficient of the Family APGAR scale was 0.889.…”
Section: Family Apgar Scalesupporting
confidence: 44%
“…39 Specifically, Family APGAR score of 0-3 is considered to be high dysfunctionality, 4-6 is moderate dysfunctionality, and 7-10 is good functionality. 40 In the present study, the Cronbach's α coefficient of the Family APGAR scale was 0.889.…”
Section: Family Apgar Scalesupporting
confidence: 44%
“…In addition, study developers evaluated whether the initial items adequately covered the target construct by pilot testing the measure with two pools of parents. Construct validity of the PSS met criteria for a good rating, as it differentiated between parents of children who were first-time juvenile offenders and parents of nonoffender children (Les Caldwell, Horne, Davidson, & Quinn, 2007) and correlated with several theoretically related constructs (e.g., parent loneliness, anxiety, marital satisfaction, family functioning). The PSS demonstrated adequate treatment sensitivity, as it reportedly decreased following a familyfocused group intervention for parents of juvenile offenders (Les Caldwell et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Results showed that there is a strong evidence base for the treatment sensitivity of parenting stress measures in relation to parent training, parent-child interaction therapy, and social skills training interventions, primarily for parents of youth with ADHD, ASD, and disruptive behavior problems (e.g., Bradshaw et al, 2018;Gonring et al, 2017;Harwood & Eyberg, 2006;Niec, Barnett, Prewett, & Shanley Chatham, 2016). A smaller but growing evidence base exists for the treatment sensitivity of parenting stress measures with respect to other interventions including mindfulness-based stress reduction programs for children with developmental delays, multiple family group intervention for juvenile first offenders, and motivational interviewing for adolescents with ADHD (Les Caldwell et al, 2007;Neece, 2014;Sibley et al, 2016). It is worth noting that none of the treatment programs reviewed herein specifically targeted parenting stress or evaluated the mechanisms underlying treatment-related reductions in parenting stress.…”
Section: Treatment Sensitivitymentioning
confidence: 99%
“…MFT with first-time juvenile offenders and sexually abusive youth and their families has shown encouraging results. Findings from three controlled studies on first-time offenders indicate improved treatment participation compared to single family and individual therapy (McKay et al, 2002), significant decrease in recidivism (eight times less) compared to a control group placed on probation (Quinn and Van Dyke, 2004), as well as reduced parental stress and improved parent-juvenile communication at the end of treatment and at threemonths follow-up (Caldwell et al, 2007). A systemic MFT programme has been developed by Keiley (2002) for incarcerated delinquent adolescents that specifically focuses on restoration of parent-adolescent attachment and on affect management.…”
Section: Social Exclusionmentioning
confidence: 99%